Innate recognition of viruses - e Sousa, Caetano Reis (Henry Stewart Talks, 2009)
Induction of the adaptive Immunity, Pattern recognition receptors: coupling innate to adaptive immunity, Induction of type I IFNs: an example of recognition of viral patterns, Cytosolic pathway for influenza virus recognition and inhibition by the viral, NSI protein, RIG-I-mediated recognition of influenza virus genomes and 5'-PPP-RNA, Cytosolic 5'-PPP-RNA as a PAMP, Plasmacytoid DC and the discovery of a second pathway for innate recognition of influenza virus, Endosomal pathways for virus recognition: TLR7, TLR9, TLR3 as a sensor of virally-infected cells